Nomophobia pada mahasiswa generasi Z: Bagaimana peranan loneliness? - Muhammad Tri Hadi Saputro; Herlan Pratikto; Suhadianto (INNER: Journal of Psychological Research, 2023)
Abstract Advances in technology have changed people’s lives. The use of smartphones can have both positive and negative impacts, one of which is nomophobia. This study aims to analyze the relationship between loneliness and nomophobia in Gen Z students. This study used a correlational quantitative method involving 216 Z generation students as participants. The data collection instrument used the nomophobia scale and the loneliness scale. The results of data analysis using Spearman’s Rho show the value of rho = 0.848 with a significance of p = 0.000 (p <0.01) so that there is a very significant positive relationship between loneliness and nomophobia in gen Z students. Suggestions for students to be more active in a social environment, for parents of students are advised to communicate more often with their children, and for future researchers it is advisable to pay more attention to the composition of the respondents. Abstrak Kemajuan teknologi telah mengubah kehidupan masyarakat. Penggunaan smartphone dapat memberikan dampak positif dan juga dampak negatif, salah satunya nomophobia. Penelitian ini bertujuan untuk menganalisis hubungan antara loneliness dengan nomophobia pada mahasiswa gen Z. Penelitian ini menggunakan metode kuantitatif korelasional yang melibatkan 216 mahasiswa generasi Z sebagai partisipan. Instrumen pengumpulan data menggunakan skala nomophobia dan skala loneliness. Hasil analisis data menggunakan spearman’s rho menunjukkan nilai rho = 0,848 dengan signifikansi p = 0,000 (p<0,01) sehingga ada hubungan positif yang sangat signifikan antara loneliness dengan nomophobia pada mahasiswa gen Z. Saran bagi mahasiswa untuk lebih aktif dalam lingkungan sosial, bagi orang tua mahasiswa disarankan untuk lebih sering berkomunikasi dengan anak, dan bagi peneliti selanjutnya disarankan lebih memperhatikan komposisi responden.